Atypical erythrocytes and platelets in a patient with a pro-thrombin mutation. (September 2014) - Pretorius, Etheresia; Vermeulen, Natasha; Bester, Janette
Abstract Prothrombin mutation G20210A, anti-phospholipid syndrome as well as iron overload has previously been shown to cause thrombotic events. The main reason for this is the involvement of these anomalies in causing hypercoagulability of the coagulation system, which frequently leads to venous and arterial thrombotic events. We report the case of a 37-year-old white female with prothrombin mutation G20210A, anti-phospholipid syndrome, as well as an increased serum ferritin level, who experienced two transient ischemic attacks and suffers from regular amaurosis fugax. We present an ultrastructural depiction of erythrocytes, platelets, and the fibrin network, to explain the clinical manifestations of the thrombotic state seen in this patient.